Ответ:
Ответ:1) х² - 10² = (х-10) (х+10)2) 6² - (9b) ² = (6-9b) (6+9b)3) (3 х) ² - (8 у) ² = (3 х-8 у) (3 х+8 у)4) (0,3 а) ² - (1,2b) ² = (0,3 а-1,2b) (0,3a+1,2b)5) х⁴у⁴-3²/4² = (х²у²-3/4) (х²у²+3/4)
Пошаговоошаго
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Ответ:1) х² - 10² = (х-10) (х+10)
2) 6² - (9b) ² = (6-9b) (6+9b)
3) (3 х) ² - (8 у) ² = (3 х-8 у) (3 х+8 у)
4) (0,3 а) ² - (1,2b) ² = (0,3 а-1,2b) (0,3a+1,2b)
5) х⁴у⁴-3²/4² = (х²у²-3/4) (х²у²+3/4)
Пошаговоошаго